Análisis de la recaudación tributaria en los juegos de casino y máquinas tragamonedas en Loreto, periodo 2015 – 2020 - Wong Lujan, Gissela (2023)
In the present investigation, the behavior of tax collection in casino games and slot machines in Loreto was analyzed, during the period 2015 – 2020, having developed a study and quantitative description - non-experimental. The study population was organized by statistical records obtained from the information provided by SUNAT on tax collection, using documentary analysis or review as a research technique; likewise, as an instrument the Registration Form was used. The behavior of collection in this sector was identified, related to the internal taxes collected by SUNAT in Perú and in the department of Loreto, from 2015 to 2020, taking 2015 as the base year, and the per capita income of the inhabitants of Loreto, finding that during the year 2020 (COVID-19 pandemic) there was less collection with an income trend below the index of the base year 2015, with a drop in collection in 2020 compared to the other periods.